Calculation of building structures and features of its automation technology - Shkurupiy, Oleksandr; Mytrofanov, Pavlo; Pashchenko, Andrii; Kozichko, Ivan (Academic journal Industrial Machine Building Civil Engineering, 2019)
Recently, the issues of evaluating the quality of building structures and predicting their reliability are becoming increasingly important, especially for the construction of industrial facilities of the old fund. Powerful mathematical methods are being developed to evaluate the performance of structures and predict their reliability, but there are no automated computer systems for such analysis. At present, programs for the determined calculation of structures have been developed, which implement methods for the resistance of materials, theoretical and construction mechanics, but they do not provide an opportunity to determine and predict reliability, especially objects of the old fund. The methods of the classical reliability theory combined with the methods of statistical modeling are used in the work, which requires the use of modern IT technologies methods with the development of appropriate software systems